Investigation of choline-binding protein of CbpD in the pathogenesis of Streptococcus suis type 2 - Zhu, Lexin; Li, Mengqing; Yu, Guijun; Zhan, Dongbo; Zeng, Wenzhen; Fu, Nanyan; Jiang, Xiaowu (Frontiers in Veterinary Science, 2024)
Streptococcus suis serotype 2 (S. suis type 2, SS2) is one of the zoonotic pathogens known to induce meningitis, septicemia, and arthritis in both pigs and humans, resulting in public health concerns. CbpD, also termed CrfP, is one of the choline-binding proteins (CBPs) that was found as a murein hydrolase in SS2 and plays crucial roles in natural genetic transformation under the control of ComRS-ComX regulatory system by a previous study. Nonetheless, the possible functions of CbpD in virulence and pathogenesis in SS2 remain unclear. In this study, a cbpD gene mutant (ΔcbpD) with its complemental strain (cΔcbpD) was constructed and further used to examine the pathogenic roles of CbpD in SS2 infection. The results showed that the CbpD deficiency leads to increased bacterial chain elongation and aggregation with little impact on the growth capability of SS2. The ΔcbpD strain represented more vulnerable to a thermo, acid, or oxidative stress. Elevated adhesion to human epithelial HEp-2 cells, decreased invasion into bEND3.0 cells, and more easily phagocytosed by murine RAW264.7 macrophages of ΔcbpD were found. The virulence of cbpD mutant was attenuated in a mouse infection model. Enhanced susceptibility within mice blood and impaired ability to colonize organs with alleviated histopathological lesions were also demonstrated as compared with wild-type SS2. It is noteworthy that the discrepant expression of multiple virulence-associated factors including serine/threonine phosphorylase Stp, anti-phagocytosis factor of transglutaminase TGase and adhesin of chaperon DnaJ, were examined resulting from the deletion of cbpD. Overall, these findings provided evidence that the CbpD factor contributes to SS2 infection and is involved in bacterial adhesion, invasion, and anti-phagocytosis processes by modulating crucial virulence-associated factors expression.